Ryzyko jako element stylu życia współczesnej młodzieży. Ujęcie teoretyczno-empiryczne - Paulina, Peret-Drążewska (Studia Edukacyjne, 2017)
The theoretical and empirical analysis is intended to address the specificityof risk categories in the present and the relevance of these issues in the light of their perception by modern youth, which is part of the analysis of young people’s lifestyles. Discussions on changes in the risk category in the present and the distinction between risk and anxiety were also discussed. Also presented are the results of our own research presenting the opinions of contemporary youth on contemporary society, taking into account the category of risk.